Follow for Now, Volume 2 More Interviews with Friends and Heroes - Roy, Christopher (punctum books, 2021)
"Follow for Now, Vol. 2 picks up and pushes beyond the first volume with a more diverse set of interviewees and interviews. The intent of the first collection was to bring together voices from across disciplines, to cross-pollinate ideas. At the time, social media wasn't crisscrossing all of the lines and categories held a bit more sway. Volume 2 aims not only to pick up where Follow for Now left off but also to tighten its approach with deeper subjects and more timely interviews. Featuring conversations with thinkers like Carla Nappi, Rita Raley, Dominic Pettman, Ian Bogost, Mark Dery, Douglas Rushkoff, and Dave Allen, and musicians like Tyler, The Creator, Matthew Shipp, Sean Price, Rammellzee, and Sadat X, as well as writers like Ytasha L. Womack, Chris Kraus, Pat Cadigan, Bob Stephenson, Simon Critchley, Simon Reynolds, Malcolm Gladwell, and William Gibson, Follow for Now, Vol. 2 is another critical cross-section of the now."